PENINGKATAN HASIL BELAJAR BAHASA ARAB DI ERA PENDEMI MELALUI METODE VIDEO BASE LEARNING SISWA KELAS X IPS SMAIT BAITUSSALAM PRAMBANAN - Shira Bella; Bayu Andri Pratama; Rasuludin Rasuludin (IAIN Ponorogo, 2021)
This research is a classroom action research that aims to find out the improvement of the results of learning Arabic through the video base learning method of grade X IPS SMAIT Baitussalam prambanan. The subject of this study was grade X students of SMAIT Baitussalam school year 2020/2021 a total of 20 students. Research is carried out with 2 cycles namely cycle I and cycle II. The research stage conducted in cycles I and II includes 4 stages, namely: planning stage, implementation stage, observation and reflection stage. In the implementation stage the researcher is slightly different because the learning is not done in the classroom but the students and teachers are in different places. Based on the results of the study in cycle I obtained the average grade value is 60.25 included in less predicate. While the result in cycle II is obtained the average grade value is 90.25 included in the high predicate. Thus, from the results of cycle I research and cycle II student learning results increased by 30%.Keywords : Learning Results; Arabi; Video Base Learning.